Adhesive incisional drapes during cesarean delivery for preventing wound infection: A systematic review and meta-analysis of randomized controlled trials. (October 2019) - Eckler, Rebecca; Quist-Nelson, Johanna; Saccone, Gabriele; Ward, Harvey; Berghella, Vincenzo
Abstract: Objective: To compare the incidence of wound infection after cesarean delivery in procedures conducted using adhesive incisional drapes verses no adhesive incisional drapes. Study Design: Searches were performed in electronic databases (MEDLINE, ClinicalTrials.gov, the Cochrane Central Register of Controlled Trials, Scopus, OVID, EMBASE, and the PROSPERO International Prospective Register of Systematic Reviews). We included randomized controlled trials comparing adhesive incisional drapes to no adhesive incisional drapes during cesarean delivery. The primary outcome of this meta-analysis was wound infection. Meta-analysis was performed using the random effects model of DerSimonian and Laird, to produce relative risk (RR) with 95% confidence interval (CI). Results: 52 publications were identified through initial search of databases and two randomized controlled trials were eligible and included in the meta-analysis. Our meta-analysis examined a total of 1943 subjects and showed a statistically significant increase in wound infections in patients in the adhesive incisional drape group when compared to the control group (RR: 1.29, 95% CI: 1.02–1.65). Conclusion: Adhesive incisional drapes may increase the incidence of wound infections after cesarean delivery. Further studies are necessary to explore this relationship in the setting of current postoperative infection prophylaxis, including broad-spectrum antibiotic coverage, skin preparation and vaginal cleansing.